Analysis of the Characteristics of TIGIT-Expressing CD3−CD56+NK Cells in Controlling Different Stages of HIV-1 Infection - Zhang, Xin; Lu, Xiaofan; Cheung, Allen Ka Loon; Zhang, Qiuyue; Liu, Zhiying; Li, Zhen; Yuan, Lin; Wang, Rui; Liu, Yan; Tang, Bin; Xia, Huan; Wu, Hao; et al. (Frontiers in Immunology, 2021)
TIGIT expression on natural killer (NK) cells is associated with dysfunction during chronic HIV infection, but the phenotype and biological functions of these cells in the context of acute HIV-1 infection remain poorly understood. Here, 19 acutely infected HIV-1 patients traced at first, third and twelfth month, and 19 patients with chronic HIV-1 infection were enrolled to investigate the phenotype and functions of TIGIT expression on NK cells. We found that TIGIT-expressing NK cells did not increase in frequency in the first, third and twelfth months of infection until chronic HIV-1 infection. The number of TIGIT+NK cells in acute infection was positively associated with HIV-1 viral load. CD96 was significantly upregulated on NK cells after acute infection for one month and in chronic infection, while CD226 was downregulated in chronic infection. Further, at different stages of infection, CD96−CD226+ cells diminished among total NK cells, TIGIT+NK and TIGIT−NK cells, while CD96+CD226− cells expanded. Reduced CD96−CD226+ cells and elevated CD96+CD226− cells among NK cells especially TIGIT−NK cells, had opposite associations with viral load in the first month of infection, as well as CD4 T-cell counts in including the twelfth month and more than two years of chronic infection. In both HIV-1-infected individuals and healthy donors, TIGIT was predominantly expressed in NKG2A−NKG2C+NK cells, with a significantly higher proportion than in NKG2A+NKG2C−NK cells. Moreover, the frequencies of TIGIT+NK cells were positively associated with the frequencies of NKG2A−NKG2C+NK cells in acute infection, chronic infection and healthy donors. Enhanced early activation and coexpression of CD38 and HLA-DR in TIGIT+NK cells were detected compared to TIGIT−NK cells, both of which were inversely associated with the decrease in CD4 T-cell counts in both acute and chronic HIV-1 infection. The ability of TIGIT+NK cells to produce TNF-α, IFN-γ and CD107a degranulation substance were consistently weaker than that of TIGIT−NK cells in both acute and chronic infection. Moreover, the functionalities of TIGIT+NK cells were lower than those of TIGIT−NK cells, except for TNF-α−CD107a+IFN-γ−NK cells. These findings highlight the phenotype and functional characteristics of TIGIT-expressing NK cells have poor capabilities in inhibiting HIV-1 replication and maintaining CD4 T-cell counts.